Identification of distinct telencephalic progenitor pools for neuronal diversity in the amygdala - Hirata, Tsutomu (2009)
The development of the amygdala, a central structure of the limbic system, remains poorly understood. We found that two spatially distinct and early-specified telencephalic progenitor pools marked by the homeodomain transcription factor Dbx1 are major sources of neuronal cell diversity in the mature mouse amygdala. We found that Dbx1-positive cells of the ventral pallium generate the excitatory neurons of the basolateral complex and cortical amygdala nuclei. Moreover, Dbx1-derived cells comprise a previously unknown migratory stream that emanates from the preoptic area (POA), a ventral telencephalic domain adjacent to the diencephalic border. The Dbx1-positive, POA-derived population migrated specifically to the amygdala and, as defined by both immunochemical and electrophysiological criteria, generated a unique subclass of inhibitory neurons in the medial amygdala nucleus. Thus, this POA-derived population represents a previously unknown progenitor pool dedicated to the limbic system.